Behavioural adaptation and road safety theory, evidence, and action edited by Christina Rudin-Brown, Samantha Jamson - Jamson, Samantha; Rudin-Brown, Christina (Taylor & Francis, 2013)
"This book presents an exhaustive compilation of state-of- the-art research and theory into the causes and consequences of behavioral adaptation in road transport/ road safety and systems. It brings together earlier and more recent theories on behavioral adaptation, combined with practical advice and methods to minimize the potential impact of behavioral adaptation on the road transport system and road user safety. This text is an essential component of any road safety library, benefiting researchers, practitioners, designers and policy-makers interested in maximizing safety while encouraging innovation and excellence in road transport-related design"--